PERFORMANCE OF AGRICULTURAL EXTENSION WORKERS IN KENDARI CITY : Kinerja Penyuluh Pertanian di Kota Kendari - Sallahuddin Salahuddin; Nurhayu Malik (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
This study aimed to describe the performance of agricultural extension workers in Kendari City. This research was conducted in Kendari City in April - June 2024. Sampling in this study was carried out using the census method. In this study, the entire research population, namely agricultural extension workers with the status of State Civil Apparatus in Kendari City, totaling 63 people, were taken as research samples. The variables of this study are the performance of agricultural extension workers which include: performance of extension workers in planning, performance of extension workers in implementation, and performance of extension workers in evaluating agricultural extension. The data obtained were analyzed quantitatively descriptively. The results of the study showed that the performance of agricultural extension workers in Kendari City was in the high category. Agricultural extension workers in Kendari City have had high performance in planning, implementing, and evaluating agricultural extension.